Proprioception in sports medicine and athletic conditioning - Ogard, W. (Strength and Conditioning Journal, 2011)
Proprioception is an important somatosensory subsystem that affects movement. Understanding proprioception and how it is affected by injury, rehabilitation, and training is crucial to instituting effective interventions for treating and preventing injuries. The aim of this article was to discuss and clarify terminology and concepts of proprioceptive function and how it is addressed in the context of sports medicine and athletic conditioning.